Photosystem I Inhibition, Protection and Signalling: Knowns and Unknowns - Lima-Melo, Yugo; Kılıç, Mehmet; Aro, Eva-Mari; Gollan, Peter J. (Frontiers in Plant Science, 2021)
Photosynthesis is the process that harnesses, converts and stores light energy in the form of chemical energy in bonds of organic compounds. Oxygenic photosynthetic organisms (i.e. plants, algae and cyanobacteria) employ an efficient apparatus to split water and transport electrons to high-energy electron acceptors. The photosynthetic system must be finely balanced between energy harvesting and energy utilisation, in order to limit generation of dangerous compounds that can damage the integrity of cells. Insight into how the photosynthetic components are protected, regulated, damaged, and repaired during changing environmental conditions is crucial for improving photosynthetic efficiency in crop species. Photosystem I (PSI) is an integral component of the photosynthetic system located at the juncture between energy-harnessing and energy consumption through metabolism. Although the main site of photoinhibition is the photosystem II (PSII), PSI is also known to be inactivated by photosynthetic energy imbalance, with slower reactivation compared to PSII; however, several outstanding questions remain about the mechanisms of damage and repair, and about the impact of PSI photoinhibition on signalling and metabolism. In this review, we address the knowns and unknowns about PSI activity, inhibition, protection, and repair in plants. We also discuss the role of PSI in retrograde signalling pathways and highlight putative signals triggered by the functional status of the PSI pool.